Religion in modern New Mexico - University of New Mexico. Center for the American West. (Albuquerque University of New Mexico Press, 1997)
The religious experiences of modern New Mexico are diverse: they range from Penitente ceremonies to "televangelists," from oriental mysticism to crystal shops, and from sacred mountains to a mega-church that seats 7,000. Taken together, these essays form an interfaith conversation about how the different religious traditions have confronted modernity and materialism. The activities of religious groups in New Mexico are also compared to national trends in such basic matters as church growth, concern for social justice, and teaching personal morality
Roman Catholicism in modern New Mexico : a commitment to survive / Carol Jensen -- Protestantism in modern New Mexico / Randi Jones Walker -- The religious culture of the Jews in modern New Mexico / Henry J. Tobias -- Competition for the native American soul : the search for religious freedom in twentieth-century New Mexico / Kathleen Egan Chamberlain -- Mormons in twentieth-century New Mexico / Leonard J. Arrington -- A rhetorical approach to Protestant evangelism in twentieth-century New Mexico /Janice E. Schuetz -- Boomer dharma : the evolution of alternative spiritual communities in modern New Mexico / Stephen Fox -- The United States and New Mexico : a twentieth-century comparative religious history / Ferenc M. Szasz.
"Published in cooperation with the University of New Mexico Center for the American West."
Essays first presented at a conference held at the University of New Mexico on September 11, 1993.
71467
Keywords: Conference papers and proceedings; New Mexico -- Religion -- Congresses; New Mexico -- Church history -- Congresses